2008
DOI: 10.1007/s12015-008-9019-z
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Adult Bone Marrow Stem Cells in Liver Disease and Delivery Approaches

Abstract: Hematopoietic stem cells (HSCs) and mesenchymal stem cell (MSCs) are two main subtypes of bone marrow stem cells. Extensive studies have been carried out to investigate the therapeutic potential of BMSCs in liver disease. A number of animal and human studies demonstrated that either HSCs or MSCs could be applied to therapeutic purposes in certain liver diseases. The diseased liver may recruit migratory stem cells, particularly from the bone marrow, to generate hepatocyte-like cells either by transdifferentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 122 publications
0
25
0
3
Order By: Relevance
“…The mechanisms by which BMSCs alleviate acute liver injury involve challenges. It has primarily been reported that BMSCs are able to differentiate into hepatocyte-like cells and thereby promote liver tissue recovery and healing (15). However, there is increasing awareness of the contribution of BMSC-induced generation of trophic molecules by paracrine action in the alleviation of acute liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which BMSCs alleviate acute liver injury involve challenges. It has primarily been reported that BMSCs are able to differentiate into hepatocyte-like cells and thereby promote liver tissue recovery and healing (15). However, there is increasing awareness of the contribution of BMSC-induced generation of trophic molecules by paracrine action in the alleviation of acute liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…The potentialities of this kind of approach are currently under consideration in several fields, as demonstrated by the growing list of publications on this topic (Corsten and Shah 2008;Granero-Molto et al 2008;Liu et al 2008;Meyerrose et al 2008;Xu and Liu 2008;and others). The rationale in the application of MSCT to RANKL-dependent ARO is that in this way the patient would receive the specific precursor cells able to differentiate into normal osteoblasts, producing in situ the cytokine RANKL, which is defective in the recipient, and thus allowing the differentiation of osteoclast precursors into normal, functional cells.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrations of the capacity of MSCs, HSCs, and EPCs to ameliorate liver injury have raised considerable interest in the use of autologous BMSC transplantation as a potential therapy for liver cirrhosis [58,90,92,97,156,157]. A number of clinical trials have investigated autologous BMSC transfusion in patients with chronic liver disease (Table 3).…”
Section: Clinical Studies Of Bmsc Transplantation For Liver Disease Imentioning
confidence: 99%